PELATIHAN RUANG TERBUKA HIJAU DENGAN PENANAMAN POHON PUCUK MERAH DI DESA PAYACUT KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Yayuk Kurnia Risna; Ridwan Iriadi; Cut Azizah; Zahrul Fuady; Nuraina (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
The environment is something that exists around life or organisms. A clean environment means no disease, less flooding, fresh, clean air, and so on. The increase in the number of building construction and the number of vehicles indirectly affects the increase in air temperature in the environment. This results in air pollution so that green open spaces are increasingly under pressure. One of the negative impacts of this is global warming and climate change. The way to reduce the effects of global warming and climate change is to increase number of trees through planting. This community service activity is green open space training by planting Red Shoot Trees in Payacut Village, District. Peusangan District. Bireuen. This activity aimed to reduce the causes of flooding, reduce air pollution, and create a green and healthy environment. Community service activities were carried out through 3 stages, namely preparation, implementation and reporting. The method of implementing activities was through lectures (question and answer) and demonstrations. The results of PKM activities were: 1) community understanding and awareness of the importance of protecting the environment, 2) increasing community motivation to care for the environment by participating in tree planting activities, and 3) creating a community that cares about greening the environment and a healthy environment through tree planting activities. This activity is carried out continuously by lecturers and students of the Master of Natural Resources and Environmental Management Study Program, Almuslim University Postgraduate Program.